Lithium Exposure and Risk of Major Neurocognitive Disorders: A Systematic Review and Meta-analysis - Huang, Qing; Ma, Xue-Qin; Chen, Hui-Fang (Journal of clinical psychopharmacology, 2024)
Published studies on the association between lithium use and the decreased risk of major neurocognitive disorders (MNCDs) have shown disparities in their conclusions. We aimed to provide updated evidence of this association. A comprehensive literature search was performed in PubMed, EMBASE, and Cochrane Library from inception until August 31, 2023. All the observational studies evaluating the association between lithium use and MNCD risk were eligible for inclusion. Pooled odds ratios (ORs) and 95% prediction intervals were computed using random-effects models. Eight studies with 377,060 subjects were included in the analysis. In the general population on the association between lithium use versus nonuse and dementia, the OR was 0.94 (95% confidence interval [CI] = 0.77-1.24). Further analysis also demonstrated that lithium use was not associated with an increased risk of Alzheimer's disease (OR = 0.69, 95% CI: 0.31-1.65). When the analysis was restricted to individuals with bipolar disorder to reduce the confounding by clinical indication, lithium exposure was also not associated with a decreased risk of MNCD (OR = 0.9, 95% CI = 0.71-1.15). The results of this systematic review and meta-analysis do not support a significant association between lithium use and the risk of MNCD.